Towards awareness of privacy and quality of context in context-based access control for ubiquitous applications - Filho, J.B.; Martin, H. (Journal of Digital Information Management, 2009)
The growing advancement of wireless communication technologies, mobiles devices, and sensors enable new oportunities for users to share resources anytime and anywhere, making access control a critical concern. Such sensor-rich environments should be able to offer distributed and dynamic access to resources according to context information, such as user's location and time. In this scenario, the access control decisions should be based also on context information. However, as context information represents real-world situations, it is associated with certain quality indicators, such as up-to-dateness and precision, which can directly affect the access control decisions. Furthermore, enforcing user's privacy policies on context information can decrease the quality of context (QoC) information used for making access control decisions. Quality of context has in fact a strong impact on the suitable behavior of contextbased access control models. Using context information with inadequate quality may increase the probability of incorrect access control decisions. Therefore, it is important to take into account also the QoC while enforcing context-based access control policies. This paper proposes a Context-Based Access Control Model that takes into account context information and its QoC indicators to grant and to adapt access permissions on resources for Ubiquitous Computing Environments. A new module to evaluate QoC indicators was integrated in our context management architecture that is being used by proposed access control model. Moreover, we present an application called PhotoMap that uses the proposed model for controlling access to photos.
Keywords: Access control model; Context-aware; Privacy; Quality of context; Ubiquitous computing